2013
DOI: 10.1002/fld.3802
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative comparison of Taylor flow simulations based on sharp‐interface and diffuse‐interface models

Abstract: SUMMARYA pressure‐driven flow of elongated bullet‐shaped bubbles in a narrow channel is known as Taylor flow or bubble‐train flow. This process is of relevance in various applications of chemical engineering. In this paper, we describe a typical simplified experimental setting, with surface tension, density and viscosity as prescribed input parameters. We compare a sharp‐interface model based on a moving grid aligned with the bubble boundary (ALE coordinates) and a diffuse‐interface model where the bubble shap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 60 publications
(89 reference statements)
1
43
0
Order By: Relevance
“…The first project focused on 2D numerics, and was therefore limited to experimental data obtained from a round capillary (since the surface tension in all experimental setups is relatively high, rotational symmetry of the bubble can then be safely assumed) [12]. Participating numerical codes were based both on a classical sharp-interface approach and also on a diffuseinterface model.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first project focused on 2D numerics, and was therefore limited to experimental data obtained from a round capillary (since the surface tension in all experimental setups is relatively high, rotational symmetry of the bubble can then be safely assumed) [12]. Participating numerical codes were based both on a classical sharp-interface approach and also on a diffuseinterface model.…”
Section: Resultsmentioning
confidence: 99%
“…Advantages include www.gamm-proceedings.com the experimental accessibility and comparability, the sensitivity to a large range of surface tensions and the practical relevance of the proposed setup. The first two studies have been performed [12,13] and showed that it was possible yet demanding to obtain agreement between the codes and the experimental data. It is planned to put detailed data of the different codes and experiments online as supplementary material to the corresponding papers as well on the SPP homepage (www.dfg-spp1506.de/taylor-bubble).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Various numerical experiments underline the full practicality of this approach-see [19]. In the benchmark paper [5] on Taylor flow, the method of [19] was successfully validated by comparison with physical experiments and different numerical approaches. Diffuse interface models for two-phase flow of incompressible viscous fluids began to interest mathematicians some 10 years ago, while the basic concept of coupling momentum equations with the Cahn-Hilliard equation had been suggested much earlier-see the famous "Model H" of Hohenberg and Halperin [22].…”
Section: A)mentioning
confidence: 95%
“…We thus demonstrate a practical approximation procedure for the phase-field model of the moving contact line problem. Encouraged by the good agreement of the diffuse interface methods with non-wetting two-phase flow experiments [32], we shall compare the method with experimental data in the near future.…”
Section: Resultsmentioning
confidence: 99%